Review of Effectiveness of Rural Water Supply Schemes in India - Misra, Smita (World Bank, Washington, DC, 2014)
The prime objective of this study is to review the effectiveness of rural water supply schemes in different states in India. A total of 10 states have been covered in the study: Andhra Pradesh, Karnataka, Kerala, Maharashtra, Orissa, Punjab, Tamil Nadu, Uttar Pradesh, Uttarakhand, and West Bengal. The study explores the extent to which expenditure on rural water supply has been effective in providing access to safe water to rural households in India. This has been assessed in terms of their reliability and adequacy, affordability, and sustainability. In addition, the study examines in detail the capital and Operation and Maintenance (O&M) cost and the extent of cost recovery in rural water supply schemes. In order to explore the effectiveness of rural water supply schemes, the study looks at the extent to which expenditure on rural water supply under various government programs gets translated into water supply infrastructure and services. This is based on an analysis of the flow of funds, institutional costs, support Organization/non-government organization (NGO) costs, and other costs associated with the programs, as well as an assessment of direct and indirect subsidies for rural water supply. Some of the questions this study seeks to address are: What are the coping strategies adopted and coping costs borne by rural households arising out of the inadequacies/limitations of the current services? How strong is the household demand for service improvement, as reflected in their willingness to pay for improved services? What are affordable payment levels for improved services?